CALLIDIOPINI BEETLES (COLEOPTERA: CERAMBYCIDAE) IN THE COLLECTION OF MUSEUM ZOOLOGICUM BOGORIENSE, INDONESIA - Yaheita Yokoi; Hiroshi Makihara; Woro A. Noerdjito (BRIN Publishing (Penerbit BRIN), 2019)
Callidiopini species in the collection of Museum Zoologicum Bogoriense, Indonesian Institute of Sciences (LIPI) were examined. Three new species of the genus Ceresium Newman, 1842, are described, i.e. C. clytinioides sp. nov., C. sugiartoi sp. nov., both from Kalimantan, and C. emarginatum sp. nov. from Papua. One new species of the genus Examnes Pascoe, 1869, from Kalimantan, E. subvermiculatus sp. nov. is described.